169 High-sensitivity troponin is a biomarker of medium term mortality in 20, 000 consecutive hospital patients undergoing a blood test for any reason. (6th June 2022) - Hinton, Jonathan; Mariathas, Mark; Gabara, Lavinia; Allan, Rick; Nicholas, Zoe; Kwok, Chun Shing; Ramamoorthy, Sanjay; Calver, Alison; Corbett, Simon; Rawlins, John; Simpson, Iain; Wilkinson, James; et al.
Abstract : Introduction: High sensitivity troponin (hs-cTn) concentrations above the manufacturer recommended upper limit of normal (ULN) are frequently seen in patients without a clinical presentation consistent with type 1 myocardial infarction. There is increasing evidence that these concentrations may act as a marker of prognosis in a range of conditions. However, previous studies have been limited because they have only included patients in whom the clinician has requested the test. The aim of this study was to assess the relationship between medium term mortality and hs-cTn concentration in a large consecutive hospital population undergoing a blood test, regardless of whether there was a clinical indication for performing the hs-cTn.Method: This single centre study included 20, 000 consecutive patients undergoing a blood test for any reason, in whom hs-cTnI was added, regardless of the clinical indication (CHARIOT population). Mortality data up to 2.25 years was obtained via NHS Digital. The association between hs-cTnI concentration and one year mortality was evaluated using Kaplan-Meier plots (with log-rank test) and Cox proportional hazards analyses. After the cohort was considered as a whole, each of the clinical areas (inpatient (IPD), outpatient (OPD), emergency department (ED)) were considered separately. Furthermore, in the IPD and ED populations, a landmark analysis was performed excluding those patients who died within 30 days to assess whether any longer term relationship was driven by short term mortality. Results: Overall, 2825 (14.1%) patients had died at 2.25 years. The mortality at 2.25 years was significantly higher if the hs-cTnI concentration was above the ULN (45.3% versus 12.3% p<0.001 (log rank) in the entire cohort (figure 1). Multivariable Cox regression analysis demonstrated that the log(10)hs-cTnI concentration was independently associated with 2.25 year mortality (hazard ratio (HR)1.69 (95%confidence interval (CI) 1.59 – 180)). This relationship was demonstrated for patients in each of the clinical areas (IPD HR 1.46 (95%CI 1.33 – 1.60), OPD HR 2.19 (95%CI 1.84 – 2.60), ED HR 1.87 (95%CI 1.68 – 2.07)). Further analysis by excluding those patients that died within 30 days demonstrated that the relationship between hs-cTnI concentration and mortality persisted and it was not driven by short term mortality. Conclusion: In a large, unselected hospital population of both in- and out-patients, the majority of whom there was no clinical indication for testing, hs-cTnI concentration was independently associated with medium term mortality. These data suggest that hs-cTnI may have a role as a biomarker of future risk. Conflict of Interest: All of the assays used in our studies were provided free of charge by beckman coulter